Impairments in Pulmonary Function in Fontan Patients: Their Causes and Consequences - Laohachai, Karina; Ayer, Julian (Frontiers in Pediatrics, 2022)
Patients with a Fontan circulation lack a sub-pulmonary ventricle with pulmonary blood flow passively redirected to the lungs. In the Fontan circulation, ventilation has a significant influence on pulmonary blood flow and cardiac output both at rest and with exercise. Children and adults with a Fontan circulation have abnormalities in lung function. In particular, restrictive ventilatory patterns, as measured by spirometry, and impaired gas transfer, as measured by the diffusing capacity of carbon monoxide, have been frequently observed. These abnormalities in lung function are associated with reduced exercise capacity and quality of life. Moderate to severe impairment in lung volumes is independently associated with reduced survival in adults with congenital heart disease. Skeletal and inspiratory muscle weakness has also been reported in patients with a Fontan circulation, with the prospect of improving respiratory muscle function through exercise training programs. In this review, we will present data on cardiopulmonary interactions in the Fontan circulation, the prevalence and severity of impaired lung function, and respiratory muscle function in this population. We will discuss potential causes for and consequence of respiratory impairments, and their impact on exercise capacity and longer-term Fontan outcome. We aim to shed light on possible strategies to reduce morbidity by improving respiratory function in this growing population of patients.